New species of hippolytid shrimps (Crustacea: Decapoda: Caridea: Hippolytidae) from a southwest Indian Ocean seamount - Nye, Verity (Zootaxa, 2013)
Two specimens representing two hippolytid genera were sampled recently from the Coral Seamount, southwest Indian Ocean, at 732 m water depth. Lebbeus ketophilos sp. nov. and Eualus oreios sp. nov. are described and illustrated and their morphologies are compared with those of previously described species. The new species are closest in morphology to L. indicus Holthuis, 1947 and E. kinzeri Tiefenbacher, 1990 respectively. They are distinguished clearly from these and other species by a suite of morphological features. This record enhances our present knowledge of seamount biodiversity and species richness of decapod crustaceans in the Indian Ocean.